THE IMPACT OF MACROECONOMIC INDICATORS ON ECONOMIC GROWTH IN THE UNITED STATES AND INDONESIA: A COINTEGRATION TEST APPROACH - Antoni Antoni (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2019)
Abstract : The aim of this subject area is whether the impact of macroeconomic indicators on economic growth in the United States and Indonesia by using the cointegration approach. The variables used are Gross Domestic Product, Foreign Debt, Export and Foreign Direct Investment from 1998-2018. The analytical method used in this research is to apply the cointegration approach and the Vector Error Correction Model (VECM). The results show that, there is a strong long-term relationship between macroeconomic variables in the two countries. Therefore, a more active macro-economic policy is recommended in both countries, especially Indonesia. This also means that the government, especially the State of Indonesia, must make better management in the public sector that supports macroeconomic policies and other variables. Keywords: cointegration, granger causality, growth, foreign direct investment, debt, export and impuls response.